PENGARUH TOURIST EXPERIENCE DAN PUNGUTAN LIAR TERHADAP MINAT BERKUNJUNG KEMBALI DI KAWASAN CIPANAS GARUT - Utami, Rosi Aprilia; Adiatma, Dani; Rukma, Deden Firman Syuyaman (Jurnal Master Pariwisata (JUMPA); Volume 10, Nomor 01, Juli 2023, 2023)
The aim of this study is to evaluate the noteworthy impact that tourist experiences and unauthorised charges have on the inclination to return to the tourism region of Cipanas.The sample consists of 100 respondents, which were collected using purposive sampling technique. The type of research conducted is quantitative, where the researcher distributed interval-scaled questionnaires to visitors and the data was subjected to analysis through the application of multiple linear regression using SPSS. as a research tool. Based on the discussion and analysis, the regression model in this study is Y = 4,443 + 0,041X1 + 0,05X2, where the regression model has a positive value, indicating that the influence of tourist experience and illegal fees on the intention to revisit is positive. Based on the partial test results, it can be inferred that the tourist experience has a notable and affirmative impact on the willingness to revisi, as seen from the results of the tourist experience variable with T-count (3.680) > T-table (1.661) and sig value < (0.05). However, the illegal fees variable has T-count (0.190) < T-table (1.661) and sig value > (0.05), which means that the illegal fees variable has no significant impact on the willingness to revisi. The simultaneous testing results indicate that both variables have a significant impact on the willingness to revisit, as seen from the F-count value (7.599) > F-table (3.090) and sig value (0.001) < (0.05). The analysis of determination shows that the contribution of tourist experience and illegal fees on the intention to revisit is 0.118 or 11.8%, which means that visitor satisfaction does not depend on tourist experience and illegal fees alone. he remaining 88.2% can be attributed to other factors that were not examined in this study, such as tourism attractions, ease of access, accomodation, and others. Keywords: tourist experience, illegal fees, revisit intention.